Mapping the Bod2 gene associated with boron efficiency in wheat - Punchana S. (Science Society of Thailand under Royal Patronage, 2015)
Genotypic variation for response to boron (B) deficiency in wheat (Triticum aestivum L.) was determined as grain set index (GSI, %) and found to be controlled by two major genes, Bod1 and Bod2. Breeding for B efficiency may be enhanced by molecular markers associated with quantitative trait loci (QTL) for B efficiency. Two mapping populations, (Bonza × SW 41) BC2 and Fang 60 × Bonza, were made from Bonza (B inefficient), SW 41 (B moderately inefficient), and Fang 60 (B efficient) parents. Leaf samples from F2 plants from each cross were used for DNA analysis. GSI was measured in F2-derived F3 families. Seven hundred and eighty-seven simple sequence repeat (SSR) markers were used. Bulked segregant analysis and QTL analysis were performed to identify the chromosomal location for B efficiency. One QTL for B efficiency was identified and mapped in (Bonza × SW 41) BC2F3, and was found to be flanked by two SSR markers, gwm192, and gwm165. This QTL is located on the long arm of chromosome 4D between gwm165 and gwm192. This QTL region corresponded for 21% of the variation in GSI, suggesting that the chromosome segment of SW 41 parent containing the Bod2 locus was inherited by the progenies and that is located on 4D. Additional markers and further examination are required to locate Bod1, the other B efficient gene. Linked markers will enable applications of marker-assisted selection for B-efficient genotypes in wheat. Copyright © 2005 ScienceAsia.